Disputes Settlement To The Measured Object Of The Returns Border Of National Land Agency Against A Neighbor's Boundary Objects In Tegal - Mohammad Irfan Rifai; Rekowarno Rekowarno; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The land has an important role in human life because it is completely cannot be separated from land. The issue of the disputes of land boundary may cause a difference of opinion; the value of the interest regarding the layout, borders and vast areas of land that is recognized is the most issue that appears frequently in the Office of land Bordering Counties. The method of the approach that is used in this study is the juridical sociological approach. This approach was conducted to understand the law in the context of the society is a non-doctrinal approach. Through this approach, the object of the law will be meant as part of the social subsystem between the subsystems of the social subsystem-other dispute resolution borders against the border returns object, in the form of legal protection, for misusing of the follow- the Government is due to gross negligence at the time of measurement wide plots of land for the creation of a letter, then the measurement of legal protection used is the preventive protection of the law, the role of the national land Agency Chief Rules Based BPN No. 3 Of 2011 is about the management and treatment of Cases of land. The agreement or the consent of the parties concerned is essential in the framework of the implementation of dispute settlement returns the border of land ownership.Keywords: Returns the Border; National Land Agency; Dispute Resolution.